Artists'-Books 1985-1987. - Schulz, Karl; Foster, Barbara; Art Department, School of Creative Arts, San Francisco State University, San Francisco (Braunschweig : Hochschule für Bildende Künste, 1987)
Bier, Rolf ; Falke, Friedhelm ; Hettich, Walter ; Rosenthal, Frank ; Austin, Antony ; Charland, William ; Cortright, Steven ; Delos, Kate ; Denkler-Gietz, Michael ; Ellis, Edie ; Golden, Alisa ; Gosebruch, Thomas ; Hass, Ian Witter ; Hüsken, Ole-Jörn ; Ihle, John ; Jelinek, Lubos ; Kim, Bong-Kil ; King, Susan ; Meyer, Michael ; Moore, Pamela ; etc.
Artists'-Books 1985-1987 : an exhibition co-sponsored by the / Eine Ausstellung des Art Department, School of Creative Arts, San Francisco State University and the / und der Hochschule für Bildende Künste, Braunschweig, The Art Department Gallery School of Creative Arts, San Francisco State University, San Francisco, September 21 - October 23, 1987 ; The Office of the Chancellor, the California State University, Long Beach, November 9 - December 11, 1987 ; The College of Creative Studies Gallery, University of California, Santa Barbara, January 5 - January 31, 1988 ; Phebe Conley Art Gallery, Department of Art California State University, Fresno, February 7 - March 7, 1988. Weitere Ausstellungen in Europa sind in Vorbereitung / Additional exhibitions are being planned in Europe.
boek